2012
DOI: 10.1128/jcm.00992-12
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Testing Algorithms at a University Hospital for Detection of Clostridium difficile Infections

Abstract: We present the evolution of testing algorithms at our institution in which the C. Diff Quik Chek Complete immunochromatographic cartridge assay determines the presence of both glutamate dehydrogenase and Clostridium difficile toxins A and B as a primary screen for C. difficile infection and indeterminate results (glutamate dehydrogenase positive, toxin A and B negative) are confirmed by the GeneXpert C. difficile PCR assay. This two-step algorithm is a cost-effective method for highly sensitive detection of to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
27
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 27 publications
(63 reference statements)
2
27
1
1
Order By: Relevance
“…The diagnostic accuracy measures for lateral-flow GDH and lateral-flow GDH-Tox were lower in our model than those of many published estimates (12,(19)(20)(21)(37)(38)(39)(40). Several studies con- Table 3 can be seen on the x axis, where the minimal cost lines intersect ($1,600 and $6,900).…”
Section: Discussioncontrasting
confidence: 41%
“…The diagnostic accuracy measures for lateral-flow GDH and lateral-flow GDH-Tox were lower in our model than those of many published estimates (12,(19)(20)(21)(37)(38)(39)(40). Several studies con- Table 3 can be seen on the x axis, where the minimal cost lines intersect ($1,600 and $6,900).…”
Section: Discussioncontrasting
confidence: 41%
“…In recently published studies in which such calculations were performed, the full benefits of molecular assays or IA tests/ EIAs used alone or in two-step algorithms were not comprehensively assessed (15,16,24). In the studies by Walkty et al and Culbreath et al, a GDH/EIA two-step algorithm was found to be the most economical approach to screening for CDI, but only the costs of reagents and consumables were taken into account (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…In recently published studies in which such calculations were performed, the full benefits of molecular assays or IA tests/ EIAs used alone or in two-step algorithms were not comprehensively assessed (15,16,24). In the studies by Walkty et al and Culbreath et al, a GDH/EIA two-step algorithm was found to be the most economical approach to screening for CDI, but only the costs of reagents and consumables were taken into account (15,16). In contrast, in the study by Chapin et al, greater savings were actually attained with direct molecular screening, compared with a Two of the three specimens with positive GenomEra C. difficile assay results but negative toxigenic culture results were confirmed as positive with the GeneXpert C. difficile PCR assay (Cepheid).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intervention also reduces laboratory workload and hospital costs and empowers clinicians to accept negative results and avoid unnecessary antibiotic treatment and patient isolation without having to wait for the results of a repeat test. Although a formal cost analysis was not done, if the cost of each test is assumed to be approximately $40 based on values reported in the literature, the 91% reduction in repeat testing equates to a savings of 1,353 tests, or $54,120, in the postintervention period, not including the additional savings in labor, vancomycin usage, hospital isolation days, and other hospital-wide costs (15,16). As institutions put limits on repeat testing for C. difficile PCR, ordering multiple tests to diagnose CDI may soon be relegated to the past.…”
mentioning
confidence: 99%